2020
DOI: 10.2169/internalmedicine.3652-19
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Encephalitis Associated with Anti-gamma-aminobutyric Acid B Receptor Antibodies Mimicking Syncope

Abstract: Autoimmune encephalitis associated with autoantibodies to the gamma-aminobutyric acid B receptor (GABABR-AE) typically involves limbic symptoms with limbic abnormalities visible in brain magnetic resonance imaging (MRI). We herein report a case of a 48-year-old man with GABABR-AE whose initial presentation was limited to syncope without limbic symptoms or MRI abnormalities. Interestingly, serial MRI also revealed no abnormalities even after the appearance of limbic symptoms. Our findings suggest that GABABR-AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For example, Ohta et al reported a case of GABA-B encephalitis with multifocal hyperperfusion in the epithelia and subcortical MRI (7). Kitazaki et al reported a case of GABA-B encephalitis with syncope (8). Yao et al summarized seven, eight and 11 patients, respectively (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ohta et al reported a case of GABA-B encephalitis with multifocal hyperperfusion in the epithelia and subcortical MRI (7). Kitazaki et al reported a case of GABA-B encephalitis with syncope (8). Yao et al summarized seven, eight and 11 patients, respectively (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…On average, a diagnosis in humans is made 2 months after symptom onset or in a time span of 1 week to 5 years ( 14). An unremarkable MRI has been reported in 26.6% of patients with GABA B R encephalitis (34,35). Interestingly, in anti-NMDA-R encephalitis, unremarkable MRIs are described in 45% of patients (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…5 Movement disorders have been described in 14.3% of patients with anti-GABABR encephalitis, the most common being myoclonus and ataxia. 4,5 Rarer clinical presentations of anti-GABABR encephalitis, limited to single case reports, include recurrent syncope, 6 and amyotrophic lateral sclerosis. 7 It is possible that the pre-existing diagnosis of PD in our patient contributed somewhat to the CBS phenotype.…”
Section: Jmdmentioning
confidence: 99%
“…4,5 Normal MRI findings despite clinical and EEG progression have also been reported. 6 Anti-GABABR encephalitis has a high mortality, especially if associated with underlying malignancy, commonly small-cell lung carcinoma. 4 Immune-mediated therapies, such as intravenous steroids, intravenous immunoglobulins and plasma exchange, with diseasemodifying therapies are used with reasonable success.…”
Section: Jmdmentioning
confidence: 99%
See 1 more Smart Citation